2002
DOI: 10.1046/j.1365-3024.2002.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses and cytokine profiles in Ascaris lumbricoides and Trichuris trichiura infected patients

Abstract: The impact of intestinal helminth infection, i.e. Ascaris lumbricoides and Trichuris trichiura, on cellular responsiveness and cytokine production was investigated in young adults. Ascaris-specific cellular responsiveness was higher in parasite-free endemic controls than in patients infected with T. trichiura, or A. lumbricoides, or patients co-infected with both parasites. Also, mitogen-induced tumour necrosis factor (TNF)-alpha, interleukin (IL)-12 and interferon (IFN)-gamma secretion by peripheral blood mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 34 publications
5
75
0
1
Order By: Relevance
“…Children are also commonly infected with intestinal helminths when climate and poor sanitation favor the life cycle and transmission of parasites. These observations suggest that Th2-polarizing helminthic infections in childhood could promote the Th2 response to H. pylori and is supported by studies indicating helminth infections inhibit Th1-promoted responses to unrelated antigens (23)(24)(25).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Children are also commonly infected with intestinal helminths when climate and poor sanitation favor the life cycle and transmission of parasites. These observations suggest that Th2-polarizing helminthic infections in childhood could promote the Th2 response to H. pylori and is supported by studies indicating helminth infections inhibit Th1-promoted responses to unrelated antigens (23)(24)(25).…”
Section: Introductionmentioning
confidence: 57%
“…Serum IgE is a polyclonal response that has been associated with antigen-specific and nonspecific immune stimulation (36). In developed countries, elevated IgE is most commonly associated with allergies (37), and in developing tropical areas, such as Tumaco, elevated IgE is most commonly associated with parasitism (23). In addition to promoting IgE levels in serum and tissues, a variety of helminth infections have been shown to induce Th2-polarized cytokine responses (23,38), which may afford protection from reinfection (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decision was taken because differences in TNF-a and IFN-g production by mitogen-stimulated PBMCs harvested from patients infected with intestinal parasites, as well as from endemic and nonendemic controls, have been reported (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Geiger et al [12] recorded that both total IgG and the subclass IgG4 were significantly elevated in response to A. lumbricoides in infected patient groups. In contrast to this, a minimal IgG4 response was detected in infected hosts in a Nigerian population [13], while Cooper et al [11] also showed that levels of Ascaris-specific IgG, IgG1 and IgG2 antibodies are positively correlated with parasite burdens.…”
Section: The Immunological Response To Ascaris Infectionmentioning
confidence: 99%